Phaenospila gen. nov. (Hymenoptera: Braconidae: Alysiinae) and three new species from Thailand - Yao, Junli; van Achterberg, Cornelis; Sharkey, Michael J.; Chapman, Eric G.; Fang, Shuqian; Aizezi, Ayizuohere; Li, Jimin (Zootaxa, 2022)
A new braconid genus belonging to the tribe Alysiini. Phaenospila van Achterberg & Yao, gen. nov. (type species: Phaenospila signator Yao, sp. nov.), is described. The genus is identified with morphological characters and a phylogenetic analysis of COI sequence data; GenBank accession numbers of fifty generated sequences from the three species are included. Three new species are described and illustrated, Phaenospila brevicarinata van Achterberg & Yao sp. nov., Phaenospila areolator Yao & van Achterberg sp. nov., Phaenospila signator Yao sp. nov. A key to the species of the genus Phaenospila is included.